DESIGN AND REAL-TIME IMPLEMENTATION OF SYNERGETIC REGULATOR FOR A DC-DC BOOST CONVERTER (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2024)
Switching DC/DC boost converters are one of the most economical devices for increasing supply voltage due to their large conversion efficiency. With the development of modern control technologies, control of DC/DC converters has become increasingly important to improve system power density and efficiency. The output voltage of these power converters must meet stringent specifications to be fast and stable. To regulate the DC/DC boost converter in the presence of disturbances, a synergistic control (SC) system derived from synergistic theory is presented in this study. Based on the state variables, the total variable manifold supports the proposed control scheme. The distinctive features of the SC system via sliding mode control are finite time convergence and chattering-free phenomena. The Lyapunov approach is used to examine the stability of the controlled system. The suggested control scheme was verified by simulation and experimentally validated using a dSPACE DS1104 card. The controller exhibits a suitable response with high performances, such as fast transient response, negligible steady-state error, and better performance under load and output voltage fluctuations.
Keywords: DC-DC boost converter; Synergetic voltage regulator; Lyapunov approach; Grid disturbances